To solve this, subtract 2 from both sides, and you end up with x = 8. :)
Determine whether the following statements are true or false. If false, explain why.
1) Point (3,2) to (3,-2) is a reflection over the y-axis.
2) A(1,3) to A'(-1,3) is a reflection over the y-axis
Answer:
see the explanation
Step-by-step explanation:
we know that
The rule of the reflection of a point across the y-axis is equal to
(x,y) -----> (-x,y)
The rule of the reflection of a point across the x-axis is equal to
(x,y) -----> (x,-y)
so
Verify each statement
1) Point (3,2) to (3,-2) is a reflection over the y-axis.
The statement is false
Because, is a reflection over the x-axis
A reflection over the y-axis will be
(3,2) -----> (-3,2)
2) A(1,3) to A'(-1,3) is a reflection over the y-axis
The statement is true
Which expression is equivalent to
First choice: m^32n^16
Hope this helps!
Answer:
The correct answer would be m^32n^16.
Step-by-step explanation:
This is because when you have a power inside parenthesis multiplied by a power outside the parenthesis, you are simply going to multiply the numbers like so:
8 • 4 = 32
4 • 4 = 16
m^32n^16
Hope this helps,
♥A.W.E.S.W.A.N.♥
find the slope between the points (-4,5) and (-8,-5)
Answer:
[tex] \frac{5}{2} \\ [/tex]
Step-by-step explanation:
[tex] \frac{ - 5 - 5}{ - 8 - - 4} [/tex]
Y - Y divided by X - X, the Y is 5 and the X is 2 (Rise over Run)
Answer:
[tex]\displaystyle 2\frac{1}{2} = m[/tex]
Step-by-step explanation:
[tex]\displaystyle \frac{-y_1 + y_2}{-x_1 + x_2} = m \\ \\ \frac{-5 - 5}{4 - 8} = \frac{-10}{-4} = 2\frac{1}{2}[/tex]
I am joyous to assist you anytime.
In recent year 34% of all college students were enrolled part time if 6.1 million college students were enrolled part time that year what was the total number of college students
The total number of college students was 17.94 million.
Step-by-step explanation:
Percentage of part time students = 34%
Number of part time students = 6.1 million
Let,
x be the total number of students
According to statement,
34% of x = 6.1 million
[tex]\frac{34}{100}x=6.1\ million\\0.34x=6.1[/tex]
Dividing both sides by 0.34
[tex]\frac{0.34x}{0.34}=\frac{6.1}{0.34}\\x=17.94\ million[/tex]
The total number of college students was 17.94 million.
Keywords: percentage, division
Learn more about division at:
brainly.com/question/11638377brainly.com/question/11921476#LearnwithBrainly
Find percent increase, round to the nearest percent
From 24 teachers to 225 pencils
Answer: 838% to the nearest percent
Step-by-step explanation:
225 - 24 =201
=201/24 * 100
= 838% to the nearest percent
Solve the equation.
a² = 100
Enter the correct answer in the boxes.
a = 10 or a = ?
Evaluate the expression –0.4(3x – 2) + StartFraction 2 x plus 4 Over 3 EndFraction for x = 4
Answer:
[tex]-0.4(3x-2)+\frac{2x+4}{3}=0\ \textrm{for}\ x=4[/tex]
Step-by-step explanation:
Given:
The expression to evaluate is given as:
[tex]-0.4(3x-2)+\frac{2x+4}{3}[/tex]
The value of 'x' is 4.
Plug in 4 for 'x' in the above expression and simplify. This gives,
[tex]=-0.4(3(4)-2)+\frac{2(4)+4}{3}\\=-0.4(12-2)+\frac{8+4}{3}\\=-0.4(10)+\frac{12}{3}\\=-4+4\\=0[/tex]
Therefore, the value of the given expression for 'x' equal to 4 is 0.
The required value of the given expression is 0 when substituting the value of x = 4 into the expression.
The expression is given as follows:
-0.4(3x - 2) + (2x + 4) / 3
Let's evaluate the given expression for x = 4:
Expression = -0.4(3x - 2) + (2x + 4) / 3
Substitute x = 4 into the given expression:
Expression = -0.4(3 × 4 - 2) + (2 × 4 + 4) / 3
Expression = -0.4(12 - 2) + (8 + 4) / 3
Expression = -0.4(10) + 12 / 3
Expression = -4 + 12 / 3
Expression = -4 + 4
Expression = 0
Therefore, when x = 4, the value of the expression is 0.
Learn more about Expressions here :
brainly.com/question/21751419
#SPJ3
Georgia's baby brother weighed less than 11 pounds when he was born. Which of the following could be the number of ounces Georgia's baby brother weighed? Select two that apply.
A
156 ounces
B
170 ounces
C
186 ounces
D
190 ounces
Answer:
Step-by-step explanation:
B :because 11 pound in Ounces is 176
What is the first step to take when solving this linear system of equations by the addition-subtraction method? 2x + 4y = 3 x + 3y =13 A) solve for y in terms of x B) solve for x in terms of y C) multiply the first equation by −2 D) multiply the second equation by −2
The right answer is Option D.
Step-by-step explanation:
Given equations are;
2x+4y=3 Eqn 1
x+3y=13 Eqn 2
When we use subtraction-addition method, we make one of the variables same with opposite signs so that only one variable remains after addition or subtraction.
In the given problem, we will multiply Eqn 2 with "-2" so that the x variables become equal and then we can add both the equations and solve for y.
Therefore,
The first step will be to multiply the second equation by -2 to solve the linear system of equations.
The right answer is Option D.
Keywords: linear equations, subtraction
Learn more about linear equations at:
brainly.com/question/8902155brainly.com/question/8955867#LearnwithBrainly
Answer:
It's D.
Step-by-step explanation:
It was correct on my unit test review.
What is the y-intercept of y = 5?
Answer:
Y- intercept is 5!
Following a translation, the measures of the angles in a pre-image are congruent to the measures of the corresponding angles in its image.
True
False
This pair of figures is similar. Find the missing side.
Answer:
x=2
Step-by-step explanation:
so if the bigger one is 16 and the other one is 4 that means you need to multiply 4 by 4 to get 16 so to find x you need to divide the 8 by 4 to find your answer
Answer:
x = 2
Step-by-step explanation:
Since the triangles are similar then the ratios of corresponding sides are equal, that is
[tex]\frac{x}{8}[/tex] = [tex]\frac{4}{16}[/tex] ( cross- multiply )
16x = 32 ( divide both sides by 16 )
x = 2
what is the simplified expression to 3.4m+2.4m
Final answer:
The simplified expression for 3.4m + 2.4m is 5.8m. You simply add the coefficients of like terms.
Explanation:
To simplify the expression 3.4m + 2.4m, we need to combine like terms. The term 'like terms' refers to terms that have the exact same variable raised to the same power. In this case, both terms have 'm' as the variable, and it's not raised to any power (which is the same as being raised to the power of 1).
Combine the coefficients (numerical parts) of the like terms:
3.4m + 2.4m = (3.4 + 2.4)m
Add the coefficients: 3.4 + 2.4 = 5.8
Therefore, 3.4m + 2.4m = 5.8m.
How many solutions does this system of equations have?
exactly one
exactly two
infinitely many
none
Answer:
exactly one
Step-by-step explanation:
1. subtract 2x from the equation 2x + y = 1
2. now you should have y= -2x + 1
3. then on the second equation subtract 4x from 4x + 2y = 2
4. now you should have 2y = -4x + 2
5. divide everything by 2
6. now you should have y = -2x + 1
7. since you got an exact answer on both of them then it is exactly one
A recipe for 12 servings of soup calls for 8 cups of chicken broth. How
many cups of broth are needed to make 30 servings of the soup?
Answer:
20 cups of broth are needed to make 30 servings of the soup.
Step-by-step explanation:
This is a typical proportion math problem.
Just set up the proportion and solve for the unknown variable, let it be x, because it's simple to use.
12/8=30/x
simplify 12/8 to 3/2,
3/2=30/x
cross product,
2*30=3*x
60=3x
x=60/3
x=20
Number of cups of broth needed for making 30 servings is 20.
What is Proportion?Proportions are defined as the concept where two or more ratios are set to be equal to each other.
Suppose we have two ratio p : q and r : s.
If both these ratios are proportional, then we can write it as p: q : : r : s.
This is same as p : q = r : s or p/q = r/s
We have,
Cups of broth needed for 12 servings of soup = 8 cups
Let cups of broth needed for 30 servings of soup = x cups
Using the concept of proportion,
12 / 8 = 30 / x
Doing the cross multiplication,
12x = 8 × 30
12x = 240
x = 240 / 12
x = 20
Hence 20 cups of broth are needed to make 30 servings of the soup.
To learn more about Proportions, click on the link given below :
https://brainly.com/question/29962935
#SPJ2
What is the y-intercept of the function f(x) = –negative StartFraction 2 Over 9 EndFraction.x + ?
The y-intercept is 1/3
Explanation:I'll assume the function is the following:
[tex]f(x)=-\frac{2}{9}x+\frac{1}{3}[/tex]
As you can see, this is the equation of a line written in Slope-intercept form. The general rule of writing lines in this form is:
[tex]y=mx+b[/tex]
Where [tex]m[/tex] is the slope and [tex]b[/tex] is the y-intercept, which is the point at which [tex]x=0[/tex]. By comparing our function with the written rule, we can say that the y-intercept is:
[tex]\boxed{b=\frac{1}{3}}[/tex]
Learn more:y-intercept: https://brainly.com/question/13289288
#LearnWithBrainly
Answer:
[tex]b=\frac{1}{3}[/tex]
Step-by-step explanation:
The given function is
[tex]f(x)=-\frac{2}{9}x +\frac{1}{3}[/tex]
This given function is a linear function, because its variables have one as exponent, we can also say that its variables are linear.
This function, as a linear one, it's represented as a line.
Additionally, the form of this function is called slope-intercept form as
[tex]f(x)=mx+b[/tex]
Where [tex]m[/tex] is the slope and [tex]b[/tex] is the y-intercept.
So, in this case
[tex]m=-\frac{2}{9}[/tex] and [tex]b=\frac{1}{3}[/tex]
Therefore, the y-intercept of the given function is
[tex]b=\frac{1}{3}[/tex]
3. In order to enter the state fair, there is
an admission cost. Each game is $3.
Steven went to the state fair, played
4 games and spent a total of $20 on
admission and games. Assume the
relationship is linear. Find and interpret
the rate of change and the initial value.
Answer:
C = 8 + 3x
The rate of change in the above equation is 3 dollars per game and it interpret the cost per game.
The initial value in the above equation is 8 dollars, which interpret the entry fee that every one person has to pay to enter the fair.
Step-by-step explanation:
Let the admission cost of the fair is $x and each game is $3.
Now, Steven went to the state fair, played 4 games and spent a total of $20 on admission and games.
So, we can write 20 = x + 4 × 3 {As the relation is linear}
⇒ x = $8
Therefore, the admission cost in the fair is $8.
Therefore, the equation that models the situation is
C = 8 + 3x ............ (1)
Where C is the total cost and x is the number of games played.
So, the rate of change in equation (1) is 3 dollars per game and it interprets the cost per game.
Again, the initial value in equation (1) is 8 dollars, which interprets the entry fee that each person has to pay to enter the fair. (Answer)
A beauty salon buys bottles of styling gel for 4.50 per bottle and marks up the price by 40% By how much does the price go up.
Answer:
It goes up my $1.80
Step-by-step explanation:
You multiply $4.50 by 0.40 and you get 1.80 and that’s how much it goes up by
By what number should -15 raise to -1 be divided so that the quotient may be equalto -15 raise to -1
Answer:
[tex](-15)^{-1}[/tex] must be divided by 1 in order to have the quotient as [tex](-15)^{-1}[/tex]
Step-by-step explanation:
Given:
Dividend = [tex](-15)^{-1}[/tex]
Quotient = [tex](-15)^{-1}[/tex]
We notice that the dividend and the quotient are equal. This means the divisor is 1.
By identity property of 1, any number divided by 1 is equal to the same number or the quotient of a number divided by 1 is equal to the number itself.
So, we can write this as:
[tex]\frac{(-15)^{-1}}{1}=(-15)^{-1}[/tex]
Thus [tex](-15)^{-1}[/tex] must be divided by 1 in order to have the quotient as [tex](-15)^{-1}[/tex] (Answer)
need some help with this please
Answer:
40 and 50
Step-by-step explanation:
We know that River's mom drove for 45 minutes. Furthermore, at x miles per hour for a time amount y, she drove 10 miles, and at x+10 miles per hour for time amount z, she drove 25 miles. We can set up the equations like this:
x*y = 10
(x+10)*z = 25
y+z = 0.75
I knew to include time as the variable because time was given at the end, and is the only way possible to solve this. Furthermore, we can multiply x and y because we drive for x miles per hour for y hours, so
[tex]\frac{x miles}{hours} * \frac{yhours}{1} = xmiles*y[/tex]
I turned 45 into 0.75 as 45 is 3/4 of an hour, and y and z are in hours.
We're kind of stuck here, so it would be nice if we could limit the variables in an equation. One way to do this would be to solve for y in the first equation, so x=10/y. Then, we can plug that into the second equation to get
(10/y+10)*z=25
Combining that with the third equation, we can solve for z in the second equation to get that 25/(10/y+10)=z, and then plug that into the third to get that
y+25/(10/y+10) = 0.75
Multiplying both sides by 10/y+10 to get rid of the denominator, we get
10+10y+25=7.5/y+7.5
Then we multiply by y to get rid of the denominator
10y+10y²+25y=7.5+7.5y
Subtracting 7.5+7.5y to get everything on one side for a quadratic equation
10y²+27.5y-7.5=0
Plugging this into the quadratic equation, we get than y either equals -3 or 0.25. It's clear that you can't have negative time, so y = 0.25
Then, 0.75-0.25=0.5=z, and 10/0.25=40, so x=40, and x+10=50 for the 2 driving speeds
help, succession formula
Answer:
[tex]a_n=-3*\left ( -\frac{2}{3} \right )^n \ n>=0[/tex]
Step-by-step explanation:
Succession can be understood as a sorted collection of values that respond to a general term or rule. We need to find if these numbers are in arithmetic progression or geometric progression.
In an arithmetic progression, every number is obtained as the previous number plus or minus a constant value called common difference. In a geometric progression, we get the next numbers as the previous one multiplied or divided by a constant value, called the common ratio.
If we try to find a possible common difference between first and second terms we get:
[tex]2-(-3)=5[/tex]
If it was an arithmetic progression, third term should be
[tex]2+5=7[/tex]
Which is obviously not true. Now let's try to find a possible common ratio by dividing second by first term
[tex]r=\frac{2}{-3}=-\frac{2}{3}[/tex]
Testing our value to find the third term we get
[tex]a_3=2*(-\frac{2}{3})=-\frac{4}{3}[/tex]
Since we have more terms to test:
[tex]a_3=(-\frac{4}{3})*(-\frac{2}{3})=\frac{8}{9}[/tex]
The given value is just as predicted
The fourth term can be accurately predicted also:
[tex]a_4=(\frac{8}{9})*(-\frac{2}{3})=\frac{16}{27}[/tex]
Now we are sure it's a geometric progression, it can easily be stated the general term of the progression is
[tex]a_n=a_1*r^n \ n>=0[/tex]
[tex]a_n=-3*\left ( -\frac{2}{3} \right )^n \ n>=0[/tex]
The ____ value of a digit is based on its location.
Answer:
place
Step-by-step explanation:
Answer:
The answer is " Place value"
Step-by-step explanation:
The place value determines the value of the digit in a number, based on its position.
A standard form number is divided into groups of three digits using commad. Each of these groups is called a period.
Enter an equation in point-slope form for the line.
Slope is O and (6, 7) is on the line.
Answer:
[tex]\displaystyle y = 7[/tex]
Step-by-step explanation:
Since the rate of change [slope] is zero, that automatically makes our equation set equal to the y-coordinate of the ordered pair, which in this case is the y-intercept.
I am joyous to assist you anytime.
What are some math equations that end up making the answer being 209
Answer:
Step-by-step explanation:
(0^209 + 1(209)/(209))^0 + 208
• What ratio is equivalent to 6 to 2? Complete the statement.
)) The ratio 6 to 2 is equivalent to the ratio
to ?
3 to 1
The ratio 6 to 2 is equivalent to the ratio 3 to 1, obtained by dividing both the numerator and denominator of the ratio by their greatest common divisor, which is 2.
Explanation:To find a ratio equivalent to 6 to 2, you simplify the ratio by dividing both numbers by their greatest common factor. In this case, the greatest common factor is 2, so 6 ÷ 2 = 3 and 2 ÷ 2 = 1. Therefore, the equivalent ratio is 3 to 1.
The ratio 6 to 2 can be simplified by dividing both numbers by their greatest common divisor, which is 2. Therefore, 6 divided by 2 is 3, and 2 divided by 2 is 1. This simplification shows that the ratio 6 to 2 is equivalent to 3 to 1. Ratios compare two quantities and can be expressed in several forms such as fractions, with a colon, or using the word "to". An equivalent ratio maintains the same proportional relationship between its components, just like how 6:2 has the same proportional relationship as 3:1.
Assume that µ = 500 and s = 100. Your study shows a sample of size 22 with a mean of 530 and standard deviation of 113. a. What is the most powerful test to use to test the hypothesis that the mean of the sample was drawn from the above Null Hypothesis Population? b. What is the value of the test statistic? c. What do you conclude using a = 0.052 tail?
Answer: using t - test value is 1.37<2.08( At 0.05 level of significance)
The mean of the sample was drawn from the population.
Step-by-step explanation:
Here sample size n=22
Given sample mean =530
Given population mean =500
[tex]t=\frac{sample mean-µ}{\frac{S}{\sqrt{n-1} } }[/tex]
given sample standard deviation s=100
a) null hypothesis:- The mean of the sample was drawn from the population µ =500
Alternative hypothesis:-
The most powerful test you can use is t - distribution.
The test statistic is
[tex]t=\frac{sample mean- µ}{\frac{S}{\sqrt{n-1} } }
here S is the standard deviation of the sample
b) The value of the test statistic
[tex]t=\frac{sample mean- µ}{\frac{S}{\sqrt{n-1} } }
substitute given values sample size n=22
sample mean =530
sample standard deviation s =100
mean of the population µ =500
the calculated value of t =[tex]\frac{530-500}{\frac{100}{\sqrt{22} } }[/tex]
the calculated value=1.3748
c) The degrees of freedom =n-1 = 22-1 = 21
The table value of t are 0.05 level of significance with 21 degrees of freedom is 2.08
The calculated value 1.37<2.08
∴ we accept null hypothesis at 0.05 level of significance
conclusion:-
The mean of the sample was drawn from the population.
A t-test is the most powerful test for this hypothesis. The test statistic value is calculated using t = (X - µ) / (s / √n). Based on a significance level of 0.05, we can conclude by comparing the calculated t-value with the critical t-value from t-distribution table.
Explanation:The subjects of this question are hypothesis testing and statistics.
To answer your question: a) The most powerful test to use to test your hypothesis is the t-test for single mean. This is because you have one sample mean, one hypothesized population mean, and the population standard deviation is not known.
b) The value of the test statistic can be calculated using the formula: t = (X - µ) / (s / √n), where X is the sample mean, µ is the population mean, s is the sample standard deviation, and n is the sample size. Plugging in your values, the formula becomes t = (530 - 500) / (113/ √22).
c) With a = 0.05, we conclude by comparing the calculated t-value with t-distribution table (df = 22-1 = 21). If the calculated t-value exceeds the critical t-value from the t-distribution table, we reject the null hypothesis.
Learn more about Hypothesis Testing here:https://brainly.com/question/34171008
#SPJ11
a punch recipe calls for equal amounts of orange and pineapple juice. pineapple juice comes in 6 ounce cans and orange juice comes in 10 ounce cans what is the least amount of each kindof juice that can be mixed with out having any left over?
Answer:
0.6 ounces
Step-by-step explanation:
A class of 32 consists of students who either have red or yellow shirts if there are 12 more people with red shirts in there are people with yellow shirt many students have red shirt
Answer:
22 people with red shirts and 10 people with yellow shirts
Triangle DEF (not shown) is similar to ABC shown, with angle B congruent to angle E and angle C congruent to angle F. The length of side DE is 6 cm. If the area of ABC is 5 square centimeters, what is the area of DEF ?
Answer:
Area of ΔDEF is [tex]45\ cm^2[/tex].
Step-by-step explanation:
Given;
ΔABC and ΔDEF is similar and ∠B ≅ ∠E.
Length of AB = [tex]2\ cm[/tex] and
Length of DE = [tex]6\ cm[/tex]
Area of ΔABC = [tex]5\ cm^2[/tex]
Solution,
Since, ΔABC and ΔDEF is similar and ∠B ≅ ∠E.
Therefore,
[tex]\frac{Area\ of\ triangle\ 1}{Area\ of\ triangle\ 2} =\frac{AB^2}{DE^2}[/tex]
Where triangle 1 and triangle 2 is ΔABC and ΔDEF respectively.
If two triangles are similar, then the ratio of the area of both triangles is proportional to the square of the ratio of their corresponding sides.
[tex]\frac{5}{Area\ of\ triangle\ 2} =\frac{2^2}{6^2}\\ \frac{5}{Area\ of\ triangle\ 2}=\frac{4}{36}\\ Area\ of\ triangle\ 2=\frac{5\times36}{4} =5\times9=45\ cm^2[/tex]
Thus the area of ΔDEF is [tex]45\ cm^2[/tex].
csc^2x – 5 csc x = 0
The solutions are [tex]\(x = n\pi\) and \(x = \sin^{-1}(1/5)\).[/tex]
To find the solutions for [tex]\( \csc^2x - 5\csc x = 0 \)[/tex], we can factor the expression:
[tex]\[ \csc x (\csc x - 5) = 0 \][/tex]
This equation is satisfied when either [tex]\(\csc x = 0\) or \(\csc x - 5 = 0\)[/tex].
1. For [tex]\(\csc x = 0\)[/tex], we know that [tex]\(\csc x\)[/tex] is the reciprocal of the sine function, and sine is 0 at multiples of [tex]\(\pi\)[/tex]. Therefore, [tex]\(x = n\pi\)[/tex] where n is an integer.
2. For [tex]\(\csc x - 5 = 0\)[/tex], solving for [tex]\(\csc x\)[/tex] gives [tex]\(\csc x = 5\)[/tex], and the sine of an angle is the reciprocal of its cosecant. Therefore, [tex]\(x = \sin^{-1}(1/5)\).[/tex]
In summary, the solutions are [tex]\(x = n\pi\) and \(x = \sin^{-1}(1/5)\).[/tex]
The complete question is probably:
What are the solutions for \( \csc^2x - 5\csc x = 0 \)?